Porphyry type systems-configuration and distribution in the Chagai metallogenic belt with a reference to the Koh-i-Dalil Copper deposit, Balochistan, Pakistan - Bhutta, Arshad M. (Journal of Himalayan Earth Sciences, 2004)
The Chagat metallogenic belt, forming the north western part of Balochistan, is well renowned for hosting several copper porphyry type systems. The most important and well-studied deposits are Saindak, Koh-i-Dalil / Reko Diq, Dashte-Kain, Durbanchah. These are distributed in the Chagai calk-alkaline magmatic belt and exhibit more or less similar tectonomagmatic and subduction related environments. Hence, the Koh-i-Dalil / Reko Diq Cu+,4u porphyry deposit is discussed as a representative study case to understand the other porphyry systems of the Chagai region. The Koh-i-Dalil complex is a large strato-volcano developed during Miocene and is spread over an area of about 25km x 20km. is encircling a number of closely spaced porphyry systems exposed in the deeply eroded wide valley. These youngest shallow emplaced intrusives are composed of quartz diorite, granodiorite, dacite porphyries Whereas the tonalite porphyries are the favorable sites for mineralization. Late andesitic and dacitic dykes are present in a swarm of tangential fractures, resulted due to the intrusion of the tonalite porphyry stocks in the surrounding strato-volcano. The deep erosion of the central caldera has exposed cross sections of the ancient volcanic sequence and, as well as, the intruded tonalite porphyry stocks which are mineralized. The hydrothermal alteration zones overlapping in a concentric manner are very well developed over each mineralized stock. The exposure of the hydrothermal alteration zones depends on the extent of the erosional level of the host porphyry stocks. These alteration zones are distinctly differentiated, from the innermost core to the outer peripheries, into i) potassium silicate zone (K-zone), ii) phyllic/sericitic zone, iii) retrograde zone and iv) propylitic zone. The central K-zone is distinguished by the presence of secondary biotite and occasionally potash-feldspar The phyllic zone, overlapping the K-zone, is characterized by the presence of sericite and quartz resulting due to the decomposition offeldspar It displays a milky white halo. The outermost zone of propylitic alteration is marked by the presence of chlorite, epidote and quartz veins. The retrograde alteration is a type of superimposed alteration activity and is not present always. But this type of alteration is well developed in the Koh-i-DaIil (East Main Ore Body) and it is distinguished by the presence of relics of secondary biotite or potash-feldspar. Copper as chalcocite and chalcopyrite is predominantly associated with the K-zone and sericitic alterations. Hypogene mineralization is scarce on the surface owing to its decomposition and subsequent dispersion and leaching. Malachite and goethite are common surface expressions. Magnetite in dissemination and veinlets is common in the sencitic zone and central dacitic core, Geo-chemical anomaly patterns were constructed based on the analysis of more than 1200 rock chip samples for copper determination. The conduction of geophysical surveys including the magnetic, gravity and induced polarization (IP) helped to ascertain the subsurface mineralization attribute. A comparative study based on the interpretative results of integrated geological, hydrothermal alterations, geo-chemical anomalies and the I.P. surveys exhibit an excellent correspondence to each other. The anomalous zone of > 1000 ppm Cu values coincide well with the K-zone and also with the retrograde zone. fie contours of the lowest values of < 500 ppm correspond with the late mineral dacite porphyry intruded in the central part of almost each ore body.